Eksplorasi Aktivitas Antimikroba Bakteri Endofit Daun Betadine (Jatropha multifida L.) terhadap Patogen Staphylococcus aureus - Arfiandi, Arfiandi; Fadjria , Neri; Nofita, Dewi; Rahmadini, Mutia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Antibiotic resistance has spurred the exploration of novel antibacterial agents, including endophytic bacteria from medicinal plants like Jatropha multifida L. (Betadine leaves), traditionally used as antiseptics. Objective: To assess the antibacterial activity of endophytic bacterial isolates from Betadine leaves against Staphylococcus aureus. Methods: A laboratory-based experimental study employing the paper disc diffusion method. Endophytic isolates were cultured in Nutrient Broth, and centrifuged supernatants were tested for inhibition zones compared to positive (chloramphenicol) and negative (Na.CMC) controls. Results: The endophytic isolate produced a 16.11 mm inhibition zone (moderate activity), while chloramphenicol showed 27.63 mm (strong activity). No inhibition was observed in the negative control. Conclusion: Endophytic bacteria from Betadine leaves exhibit potential as natural antibacterial agents, though their efficacy is lower than standard antibiotics. Further development requires active compound characterization and toxicity studies.